2015
DOI: 10.1007/s00167-015-3804-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the feasibility of arthroscopic visualization of the lateral ligament of the ankle: a cadaveric study

Abstract: Arthroscopic identification of the ATFL, CFL and their corresponding footprints can be considered safe and reliable. Tunnels entrances, in preparation for arthroscopic ligament reconstruction, are precisely positioned. Arthroscopic anatomical ligament reconstruction is a feasible option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 14 publications
(18 reference statements)
1
37
0
1
Order By: Relevance
“…There is also a published technique to perform an arthroscopic ligament reconstruction using gracilis autograft which could be used in patients with moderate to severe ankle instability [79]. A cadaver study demonstrated that tunnels could realistically be placed within 4 mm of the true ATFL and CFL footprints [80]. Despite positive results published in the literature, the highest recommendation in a systematic review on minimally invasive surgical techniques for chronic lateral ankle instability was grade C (poor-quality evidence) [81].…”
Section: Arthroscopic Ligament Repairmentioning
confidence: 99%
“…There is also a published technique to perform an arthroscopic ligament reconstruction using gracilis autograft which could be used in patients with moderate to severe ankle instability [79]. A cadaver study demonstrated that tunnels could realistically be placed within 4 mm of the true ATFL and CFL footprints [80]. Despite positive results published in the literature, the highest recommendation in a systematic review on minimally invasive surgical techniques for chronic lateral ankle instability was grade C (poor-quality evidence) [81].…”
Section: Arthroscopic Ligament Repairmentioning
confidence: 99%
“…One of the difficulties in performing arthroscopic ankle ligament reconstruction is the limited working space. 13 Although extensive extra-articular dissection may be helpful to enlarge the working space, it is harmful for tissue healing. Sustained fluid exudates and incision dehiscence would be highly anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Because the anterior talofibular and calcaneofibular ligaments are both extra-articular structures, there is very little room for visualization and instrument maneuverability even though an extra-articular working space has been made. 13 We have explored this technique from 2010, and many complications, such as tunnel malposition, cartilage injury, graft loosening, and incision dehiscence, have been found. Therefore, we have revised this technique repeatedly, and the complications have been decreased.…”
mentioning
confidence: 99%
“…Operacijsko liječenje mekotkivnog anterolateralnog sindroma sraza sastoji se od artroskopske anterolateralna sinovijektomije i redukcije nabujalog vezivnog tkiva. Uz sinovijektomiju, artroskopija omogućava identifikaciju i stupnjevanje lezija prednjeg talofibularnog ligamenta te njihovo adekvatno liječenje 28,29 . Artroskopsko liječenje omogućuje brži oporavak pacijenata te raniji povratak u punu radnu i sportsku aktivnost.…”
Section: Etiologijaunclassified